Work-Life Balance in the Digital Age: How Work Flexibility Reduce Stress? - Sultan, Zulkifli (Universitas Medan Area, 2025)
This study aims to analyze leadership in the digital era, work flexibility, and work-life balance which are closely related to employee work stress levels. The research approach uses a quantitative approach with the Structural Equation Modeling (SEM) method using the AMOS tool. Data were collected from 150 respondents at election organizing institutions through questionnaires. The results of the study indicate that digital leadership has a significant effect on work flexibility and work-life balance, but does not affect work stress reduction. In addition, work flexibility has a relationship with work-life balance but does not significantly affect work stress reduction. However, work-life balance can affect employee stress reduction. Implications for policy makers, with the importance of digital leadership in encouraging a work flexibility system that can balance work life, so that it is necessary to create a healthier and more productive workplace. Organizations need to consider work system strategies that focus on work-life balance to avoid increased stress; therefore, flexible work is needed that is integrated with the leader's digitalization capabilities.